Stres psikososial dan kejadian kandidiasis vulvovaginalis pada wanita pekerja seks di Banyumas - Leyna Chunaifa; Yayi Suryo Prabandari; Baning Rahayujati (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Psychosocial stress and vulvovaginal Candidiasis among female sex workers in Banyumas PurposeThis study aimed to determine the relationship between psychosocial stress with candidiasis vulvovaginalis (KVV) incidence in female sex workers (FSW).MethodsThe research design was a case control study conducted in health center clinics in the Banyumas District. The sample size was 164 FSW (82 cases & 82 control). The research instrument was structured questionnaires, Social Readjustment Rating Scale (SRRS), laboratory equipment and microscopes for inspection KVV. Data analysis used logistic regression tests to calculate odds ratios (OR), confidence interval (CI), and p value.ResultsThe multivariate analysis showed that stress was not KVV risk factors, and the risk factors that contribute to the occurrence of KVV in FSW were oral sex (OR = 3.31, 95% CI = 1.60 to 6.83, p-value = 0.001) and smoking more than 10 cigarettes/day (OR = 2.33, 95% CI = 1.2 to 4.59, p-value = 0.014).ConclusionsThe risk factors of KVV were oral sex and smoking ≥ ten cigarettes/day. We recommend to avoid oral sex and smoking < ten cigarettes/day to avoid the risk of KVV infection.